Incidental English Learning and Linguicism: A Case Study of an Indonesian Child of a Multilingual Family - Da Silva , Anna Marietta (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The incidental learning of English among Indonesian children from exposure to home television movies has been a common phenomenon within the last two decades. A lot of young Indonesian children speak English fluently before entering schools because of their frequent TV viewing. This is seen as a great advantage for the children’s education and future. Nevertheless, in the context of Indonesian schools, when a student is fluent in English but not in Indonesian, they may face some serious problems. Based on Hulstijn’s (2013) incidental learning and Skutnabb-Kangas’ (2015) linguicism, this study investigates the case of an Indonesian child to try to identify the possible causes of the child’s English acquisition as a mother tongue regardless of the use of Indonesian as the main home language. A series of semi-structured interviews and a document analysis were used. Pedagogical recommendations relevant to the findings are provided.